Synthesis and Spectral Studies on Lanthanide Mixed Complexes. - Y. SUBHEDAR, MRS.; RAMACHANDRA RAO, V. (Asian Journal of Chemistry, 2010)
A few mixed complexes of La (III), Pr(III), Nd(III), Sm(III), Gd(III) and Dy(III) using orthophenylene-diamine and 2,2´-bipyridyl as primary ligands and N-phenylthiourea and N-N´-diphenylthiourea as secondary ligands have been prepared. They are characterised by a study of elemental, spectral, conductivity and thermal analysis. The nature of bonding has been established by a study of infra-red spectra and it was observed that while the primary ligands are coordinated through nitrogens, thus acting as bidentate ligands and the secondary ligands are coordinated through sulphur acting as a unidentate ligand.